Enhancing Student Engagement through Project-Based Learning and Technology Integration - Bisri Musthofa; Abdullah Mubarok; Syarifatul Fitri Hidayah; Ahmad Sunoko (Kopertais Wilayah X Jawa Tengah, 2025)
Although initial research suggests that Project-Based Learning (PJBL) and technology integration enhance student engagement and critical thinking, there is a lack of comprehensive long-term evidence on their effective adaptation in resource-constrained elementary schools. This study directly examines how PJBL combined with technology can foster deeper learning and knowledge retention in such settings. Using qualitative methods, including semi-structured interviews and classroom observations at An-Nawawiyyah Islamic School, this research provides clear evidence that PJBL, when linked to real-life problems and supported by technology, significantly boosts student engagement and understanding. However, persistent challenges—limited resources, insufficient staff training, and difficulty maintaining innovative teaching—hinder broader impact. This study contributes by clarifying how PJBL with technology can drive more meaningful learning in challenging contexts and provides an empirical basis for shaping relevant teacher development and curriculum policies. Further research should explore the long-term and comparative effectiveness of these strategies in diverse Indonesian schools.